2021
DOI: 10.3352/jeehp.2021.18.23
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis comparing the tele-objective structured clinical examination and the in-person assessment in Australia

Abstract: Purpose: It aimed to compare the use of the tele objective structured clinical examination (teleOSCE) with in-person assessment in high-stakes clinical examination so as to determine the impact of the teleOSCE on the assessment undertaken. Discussion follows regarding what skills and domains can effectively be assessed in a teleOSCE. Methods: This study is a retrospective observational analysis. It compares the results achieved by final year medical students in their clinical examination, assessed using the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 96 Due to the COVID-19 pandemic, many face-to-face OSCEs were converted to an online or hybrid format. 97 , 98 , 99 , 100 , 101 Experiences from Nurse Practitioner students 102 were positive and it highlighted that the interactive Virtual OSCE was deemed an extremely effective tool for virtual evaluation of various clinical competencies. Similar positive findings were also echoed by Farrell et al.…”
Section: Introductionmentioning
confidence: 99%
“… 96 Due to the COVID-19 pandemic, many face-to-face OSCEs were converted to an online or hybrid format. 97 , 98 , 99 , 100 , 101 Experiences from Nurse Practitioner students 102 were positive and it highlighted that the interactive Virtual OSCE was deemed an extremely effective tool for virtual evaluation of various clinical competencies. Similar positive findings were also echoed by Farrell et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many educational facilities for healthcare professionals, including residents, medical, nursing, pharmacy, and dentistry students, rapidly transitioned from traditional in-person OSCEs to virtual OSCEs (also described as remote OSCE, online OSCE, or tele-OSCE) (Felthun et al, 2021a;Malau-Aduli et al, 2022). These virtual OSCEs are satisfactory, feasible, and cost-effective as per survey results (Langenau et al, 2014;Shaban et al, 2021;Shaiba et al, 2021), questionnaire feedbacks (Skrzypek et al, 2022;Motkur et al, 2022;Garofalo et al, 2023), empirical analysis (Felthun et al, 2021b;Minty et al, 2022), and descriptive qualitative studies (Shorbagi et al, 2022;Saad et al, 2022;Thampy et al, 2022;). Although three studies assessed the reliability of virtual OSCEs by calculating Cronbach's alphas, and they were about 0.80 (Oliven et al, 2011(Oliven et al, , 2021Porto et al, 2023), a reliability analysis based on G-theory is yet to be reported (Kunutsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The main changes in teaching methods have included problembased learning aimed at learners' problem-solving skills, judgment, and analytical skills [2,3], team-based learning, which emphasizes cooperative learning, and flipped learning, which allows students to learn basic knowledge before class [4,5]. Changes in educational evaluation have included performance evaluations such as objective structured clinical examinations [6,7,8] and clinical performance examinations [9], which actually evaluate students' performance in clinical situations, criterion-referenced assessments, which evaluate whether individual students have reached their set outcomes, formative assessments aimed at providing feedback to confirm students' level of improvement, and progress tests, which check the degree to which students improve as they progress through the program [10,11]. The changes in medical education as described above have led to more demands than ever to change the role of the teacher in medical education [12].…”
mentioning
confidence: 99%